Agricultural commodity projections, 1970-1980 : volume 2, part 1-general methodology, part 2-statistical appendix - Food and Agriculture Organization of the United Nations (Rome : Food and Agriculture organization of the United Nations, 1971)
This present volume contains a description of the methodological approach used in the projections study and a statistical appendix of background tables.
Includes bibliographical references.
hza 01/02/2019
Loans
Keywords: Farm produce